I am not Starfire - Tamaki, Mariko (DC Comics, 2021)
"Seventeen-year-old Mandy, who dyes her hair black and hates almost everyone, is not like her mother, the tall, sparkly alien superhero Starfire, so when someone from Starfire's past arrives, Mandy must make a choice about who she is and if she should risk everything to save her mom."--Publisher's website.